Imperative for generating enabling environment for promotion of direct marketing in light of recent farm reform law in Indian Agriculture - Chintala, G R (Indian Farming, 2021)
Indian Agricultural Marketing is marred by long inefficient supply chain that increased the price spread between producer and consumer and have serious ramification for income realisation of farmers and affects economic growth also. In this scenario, deregulating the market structure and bringing in more competition will help in optimising the spread between price paid by consumer and received by producer.